2011
DOI: 10.1057/bm.2011.39
|View full text |Cite
|
Sign up to set email alerts
|

On the validity of measuring brand images by rating concepts and free associations

Abstract: Keith Vorstreceived his PhD from Michigan State University and is an associate professor of Industrial Technology in the Orfalea College of Business, Cal Poly. Dr Vorst directs the development and design and biodegradable components of packaging projects at Cal Poly. He has worked for three major packaging companies and as consultant for a major automotive manufacturer; and he has published extensively in ABSTRACT This article provides a validity assessment of measuring brand image by free association using ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…New web‐enabled research tools that capture the benefits of real‐time creative idea generation from very large virtual groups address the small group size of the collaborative workshop approach noted above, as well as the small group size limitations of observational and one‐on‐one or focus group interview methodologies. Danes et al (2010, 2011) present an innovative, web‐based ideation tool that enables participants to dynamically generate and evaluate ideas. The tool offers market and packaging researchers the potential to connect with and solicit ideas from very large numbers of respondents, and also permits respondents to evaluate and share ideas with each other.…”
Section: Methodologies Used To Gain Consumer Insights On Package Designmentioning
confidence: 99%
See 2 more Smart Citations
“…New web‐enabled research tools that capture the benefits of real‐time creative idea generation from very large virtual groups address the small group size of the collaborative workshop approach noted above, as well as the small group size limitations of observational and one‐on‐one or focus group interview methodologies. Danes et al (2010, 2011) present an innovative, web‐based ideation tool that enables participants to dynamically generate and evaluate ideas. The tool offers market and packaging researchers the potential to connect with and solicit ideas from very large numbers of respondents, and also permits respondents to evaluate and share ideas with each other.…”
Section: Methodologies Used To Gain Consumer Insights On Package Designmentioning
confidence: 99%
“…The tool offers market and packaging researchers the potential to connect with and solicit ideas from very large numbers of respondents, and also permits respondents to evaluate and share ideas with each other. The premises and benefits of dialogr.com as a qualitative research methodology are enumerated in Danes et al (2010, 2011).…”
Section: Methodologies Used To Gain Consumer Insights On Package Designmentioning
confidence: 99%
See 1 more Smart Citation
“…While some authors have defended the use of the former (Gardner & Levy, 1955;Durgee & Stuart, 1987;Danes, Hess, Story, & Vorst, 2012), others have opted for the latter, and the majority of authors have suggested the use of mixed techniques for image studies, combining qualitative and quantitative tools during the different study phases (Churchill, 1979;Zaichkowsky, 1985;Sanz de la Tajada, 1994;Low & Lamb, 2000;Del Rio, Vazquez, & Iglesias, 2001;Martinez & De Chernatony, 2004;Dolnicar & Grün, 2007;Koubaa, 2008;Park, 2009;Huang, 2010); (2) Although there are scales that allow for the measurement of partial dimensions of brand image, there is yet to be an agreement on a standard set of attributes; that is, items to be included in a scale for measuring the overall image of any type of brand, regardless of the specific brand product category; (3) Dobni and Zinkhan (1990) summed up the process that is typically followed when studying brand image using combined qualitative and quantitative instruments. Once again, the lack of agreement as to a specific technique and measurement scale is evident.…”
Section: Literature Review Brand Imagementioning
confidence: 99%